Efektivitas Penampang Drainase Berdasarkan Akumulasi Air Hujan Ruas Jalan yang Rawan Genangan di Jl. Mastrip/Jl. Selomangleng, Kota Kediri - Sinta Nur Aini; Sony Susanto (Jurnal Talenta Sipil, 2026)
The Universitas Kadiri area in Kediri City frequently experiences surface water accumulation during heavy rainfall due to insufficient drainage capacity, sedimentation, vegetation growth, and deterioration of channel wall plaster. These conditions indicate the need for an evaluation of drainage channel performance in accommodating rainfall runoff. This study aims to assess the effectiveness of the existing drainage cross-section and to design a more adaptive and efficient channel section. The methods employed include field surveys, hydrological analysis using the Rational Method, and hydraulic analysis based on the Manning equation. The results show that the design discharge of 0.865 m³/s cannot be fully conveyed by the existing channel, which has a capacity of only 0.59 m³/s. The proposed adaptive trapezoidal section, with a bottom width of 0.80 m, height of 0.70 m, and slope of 0.008, increases the channel capacity to 2.15 m³/s, which is 2.49 times greater than the current condition. Economically, the redesign also yields a cost efficiency of up to 47%. Overall, the findings indicate that the proposed channel design is more effective, hydraulically efficient, and suitable for flat-topography areas. Furthermore, it aligns with the principles of the Sustainable Drainage System (SuDS) to support sustainable stormwater management in the Universitas Kadiri area.